Sprinting activities and distance covered by top level europa league soccer players - Andrzejewski, M.; Chmura, J.; Pluta, B.; Konarski, J. M. (International Journal of Sports Science and Coaching, 2015)
This study presents a detailed analysis of sprinting activities and distance covered by professional soccer players in two seasons of the Europa League competition. The investigation considered such variables as the mean sprinting distance covered, duration of the rest pause between sprinting activities and maximal running speed recorded during the match. The study involved 147 soccer players participating in 10 matches played at one ground in the 2008-2009 and 2010-2011 Europa League seasons. Players` performance data were divided into two halves of matches and five playing positions. The study was carried out using data from Amisco Pro (version 1.0.2.).